PSYCHOLOGICAL TESTING AND ASSESSMENT IN THE MILITARY - Nwafor, Chidozie Edwin; Atalor, Adesuwa (Practicum Psychologia, 2018)
Psychological testing and assessment is one of the most important contributions of psychology to the military. The efficacy of testing and assessment in predicting and optimizing military goals were experienced during both World War I and 11. Ever since, more advances and applications of psychological techniques gave rise to the official launching of an area of psychology called Military Psychology. This field has helped in describing, explaining, predicting and modifying military behaviors. Specifically, psychological testing and assessment is used in selection, placement, promotion and diagnosis in the military.